The Epidemiology of HIV in Oman, 1984-2018: A Nationwide Study from the Middle East - Ali Elgalib; Samir Shah; Adil Al-Wahaibi; Zeyana Al-Habsi; Maha Al-Fouri; Richard Lau; Hanan Al-Kindi; Bader Al-Rawahi; Seif Al-Abri (Springer, 2020)
We used population-based data on all diagnosed people living with Human Immunodeficiency (HIV) reported to the National AIDS Programme in 1984-2018 to describe the HIV epidemiology in Oman. A total of 3060 Omanis were diagnosed with HIV from 1984 to 2018. The proportions of new infections attributed to sexual contact accounted for 56.3% (376/668) in 1984-1996 compared with 80.7% (630/780) in 2013-2018. Of 1417 patients with a documented CD4 count at the entry of care, 45.3% had a baseline CD4 count of <200 cells/mm3. Compared with heterosexuals, homosexuals had higher rates of advanced HIV disease [42.7% (388/908) vs 50.4% (136/270), respectively]. Rates of advanced disease and death within a year of HIV diagnosis rose consistently with age at diagnosis. Approximately half (48.8%) of the patients diagnosed in 1984-2018 had died by December 2018. The majority (85.6%; 572/668) of people who were diagnosed in 1984-1997 had died compared with 12.7% (99/780) of those diagnosed in 2013-2018. However, people died more recently had a higher proportion of death within a year of HIV diagnosis [74.7% (74/99) in 2013-2018 compared with 13.8% (79/572) in 1984-1996]. This study shows that the HIV epidemic in Oman is a low-prevalence one. Of concern, a large proportion of new HIV diagnoses continued to present late, which has resulted in a substantial increase in short-term mortality over the past 20 years. Nevertheless, we observed a remarkable decline in overall mortality over time, which may be explained by the improvement in the quality of HIV care in Oman.